KEMITRAAN KEHUTANAN ANTARA PERUM PERHUTANI WILAYAH KPH BANYUMAS TIMUR DENGAN LMDH WANA SWAKARYA DESA KALIPUTIH - Unitacasya Dwi Mahardika; Gholibudin Zuhairmanto; Agoes Djatmiko; Elly Kristiani Purwendah (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2025)
This study aims to analyze the legal form and implementation of forest management in the Perhutani Forestry Partnership scheme in the East Banyumas Forest Management Unit (KPH) area, with a case study in Kaliputih Village, Purwojati District, Banyumas Regency. The main problem formulated is What is the legal form of forest management in the Perhutani Forestry Partnership in the area and How is forest management implemented in the scheme. This study uses an empirical juridical method with analytical descriptive specifications, collecting primary data through interviews, observations, and documentation, as well as secondary data from laws and regulations and related literature. The results of the study indicate that the legal form of forest management is based on a regulatory hierarchy starting from the 1945 Constitution, Law No. 41/1999, Law No. 6/2023, Government Regulation No. 23/2021, Government Regulation No. 72/2010, Ministerial Regulation of the Environment and Forestry No. 9/2021, to Perdir Perhutani No. 13/2023 and No. 6/2024, which regulates the transition from Joint Community Forest Management (PHBM) to Perhutani Forestry Partnership (KKP/KKPP). Field implementation involves activities such as pine resin tapping, land use under stands (PLDT), and jenitri agroforestry, but is still dominated by old patterns based on social customs without cooperation agreements (PKS) that fully comply with the new regulations. The main obstacles are the institutional readiness of the Forest Village Community Institution (LMDH) and the Social Forestry Community Cooperative (KMPS), understanding of regulations, and administrative adjustments. The study concluded that forest management in Kaliputih Village has been productive and ecologically sustainable, but is still in the transition process towards more formal and accountable governance. Recommendations are given to strengthen communication, administrative assistance, institutional capacity building, and forest economic diversification to support the sustainability of inclusive and sustainable management.